A Christian Perspective on Islamic Concepts of Jihad, Iman And Islam in the Context of Mindanao Peace Process - Narciso, Jerson Benia (Al-Albab, 2024)
This paper is an excerpt of a full-blown study that the author did on the role of religion in the peace process in Mindanao of Southern Philippines. It attempts to understand and analyze Islamic concepts of Jihad, Iman and Islam and their significance to the problem of armed conflict in Mindanao. Analyses of these concepts is based mainly from the perspective of Islamic liberation theology specifically on the works of Farid Esack, Asghar Ali Engineer, and Fazlur Rahman, whose thoughts on the subject are seen to have more relevance towards development of a contextual Islamic theology of peace and liberation that is reflective of the historical, socio-political, cultural, and economic conditions in Mindanao of Southern Philippines. The study attempts to understand the meanings of Jihad, Iman and Islam and draw out essential and significant theological, ethical, and political principles and values which are relevant to the issues of conflict in Mindanao of Southern Philippines, and the role of religion in the peace process. Based on the principles and values derived from the study of the said Islamic concepts, the study attempts to construct a theological and political agenda that is informed by the historical, social, and political context in Mindanao of Southern Philippines.